Convenient Synthesis of Benziodazolone: New Reagents for Direct Esterification of Alcohols and Amidation of Amines; Molecules; Vol. 26, iss. 23 - Shea M. T. Michael; Rohde G. T. Gregory; Vlasenko Yu. A. Yuliya Aleksandrovna; Postnikov P. S. Pavel Sergeevich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Zhdankin V. V. Viktor Vladimirovich; Saito Akio; Yoshimura A. Akira (2021, 2021)
Title screen